Nano ceramic paint, nano ceramic coating and preparation method and application thereof

Through the use of nanoceramic coatings, the existing coatings are easily left with oil and poor anti-corrosion and durability in high temperature environments, forming a dense mesh-like structure coating, realizing the easy cleaning and high-temperature resistance of kitchen utensils.

CN118791894BActive Publication Date: 2024-12-20INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411267933.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-20
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

Existing paints are prone to residual oil and dirt in high temperature environments, which are difficult to clean, and the coating has poor corrosion resistance and durability, and are not suitable for high-temperature use environments.

Method used

Using nanoceramic coatings, including silicon sol solution, polysiloxane and additives, the additives contain nanopowders such as nanoalumina, copper nanochromite, nanomanganese dioxide and nanographite, through spraying and dual temperature zones The curing treatment forms a dense mesh-like coating, reducing the risk of self-cracking of the coating and enhancing high temperature and oil stain resistance.

Benefits of technology

It realizes the comprehensive performance of the coating that is easy to clean, anti-oil, anti-ion penetration corrosion, wear resistance, scratch resistance and high-temperature oxidation failure, and is suitable for kitchen utensil protection in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118791894B_ABST
    Figure CN118791894B_ABST
Patent Text Reader

Abstract

The present invention provides a nano ceramic coating, a nano ceramic coating and a preparation method and application thereof, and relates to the technical field of coating materials. The nano ceramic coating comprises: a silica sol solution, polysiloxane and an additive; the additive comprises a filler, and the filler is a nano powder; wherein the weight ratio of the silica sol solution, the polysiloxane and the additive is 1:0.5~0.8:1~2. The present invention uses silica sol and polysiloxane as film-forming agents, and crosslinks the silica sol and the polysiloxane to form a bond, thereby reducing the excessive tensile stress caused by the bond contraction between the sol particles and the surface of the substrate, and avoiding the self-cracking of the formed coating; at the same time, using nano powder as a filler, the molecular gap after the silica sol is dehydrated and condensed, and the coating of the mesh structure formed relatively is pinned to improve the compactness of the coating, ensure that the formed coating has no micro cracks, avoid oil and dirt remaining in the coating, and ensure good easy cleaning and long-term durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating materials, and in particular relates to a nano ceramic paint, a nano ceramic coating, and a preparation method and application thereof. Background Art

[0002] Due to the influence of high temperature, grease and oil stains are very easy to adhere to the surface or inner wall of kitchen appliances such as gas stoves, ovens, pots, and range hoods. Currently, these kitchen appliances are mainly protected by spraying coatings.

[0003] At present, the coatings used for kitchen utensils mainly include the following related technologies: The first related technology uses silicate coatings. However, the disadvantages of silicate coatings are that they are not dense, and they are prone to foaming after high-temperature use. Holes are formed inside the coating, resulting in oil and grease remaining in the holes, making it difficult to clean. After using detergents, the base metal corrodes and causes the coating to fall off, which has problems with corrosion resistance and durability. The second technology uses phosphate, epoxy-modified silicone resin powder and high-temperature resistant curing agent powder to prepare coatings. The formed coating can play a role in high-temperature corrosion resistance, but does not have the function of easy cleaning and oil resistance. The third technology uses a fluorine-containing polymer with a double-end silane structure, which is an organic coating with certain wear resistance and easy cleaning properties, but is suitable for use at room temperature or in a low temperature environment, and is not suitable for high-temperature use environments such as gas stoves and ovens.

[0004] In summary, the coating prepared by the coating of the prior art has at least the following technical problems:

[0005] (1) It is easy to retain oil and dirt, which is difficult to clean;

[0006] (2) The coating is easy to fall off and has poor corrosion resistance and durability;

[0007] (3) Not suitable for use in high temperature environments. Summary of the invention

[0008] Therefore, the present invention provides a nano ceramic paint, a nano ceramic coating and a preparation method and application thereof, the main purpose of which is to solve the technical problem that the existing coatings are prone to residual oil stains and are difficult to clean.

[0009] In order to solve the above problems, on the one hand, the present invention provides a nano ceramic coating, the nano ceramic coating comprising: a silica sol solution, polysiloxane and an additive; wherein the additive comprises a filler, and the filler is a nano powder;

[0010] Wherein, the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5~0.8:1~2.

[0011] Furthermore, the filler includes nano-aluminum oxide powder, nano-copper chromite powder, nano-manganese dioxide powder and nano-graphite powder.

[0012] Furthermore, the additives also include a dispersant and a defoaming agent; wherein the dispersant includes at least one of methanol, isopropanol, and propylene glycol methyl ether.

[0013] Furthermore, the silica sol solution comprises the following components in parts by weight: 60-70 parts of deionized water and 30-40 parts of nano-silicon dioxide particles;

[0014] The polysiloxane includes polydimethylsiloxane;

[0015] The additive comprises the following components: 5-10 parts of water, 3-8 parts of nano-aluminum oxide powder, 15-30 parts of nano-copper chromite powder, 3-5 parts of nano-manganese dioxide powder, 6-10 parts of nano-graphite powder, 20-25 parts of methanol, 10-15 parts of isopropanol, 10-15 parts of propylene glycol methyl ether and 3-5 parts of defoaming agent.

[0016] Furthermore, the average particle size D50 of the nano silicon dioxide particles is less than 20 nm; the average particle size D50 of the nano aluminum oxide powder, nano copper chromite powder, nano manganese dioxide powder, and nano graphite powder is less than 30 nm.

[0017] In another aspect, the present invention provides a method for preparing any of the above-mentioned nano-ceramic coatings, comprising:

[0018] The silica sol solution and polysiloxane are mixed to obtain a mixed solution, and then the mixed solution is mixed with an additive to obtain a nano ceramic coating.

[0019] Furthermore, before mixing the silica sol solution and the polysiloxane, the method further comprises:

[0020] The silica sol solution is dispersed for at least 1 hour using a high-speed disperser at a speed of 400-500 r / min.

[0021] In another aspect, the present invention provides a use of any of the above-mentioned nano-ceramic coatings, wherein the nano-ceramic coating is sprayed onto a substrate to form a nano-ceramic coating on the substrate.

[0022] Furthermore, the substrate includes a gas stove and an oven.

[0023] In another aspect, the present invention provides a nano ceramic coating, wherein the nano ceramic coating is formed by spraying any of the above-mentioned nano ceramic coatings on the surface of a substrate.

[0024] In another aspect, the present invention provides a method for preparing any of the above-mentioned nano-ceramic coatings, comprising the following steps:

[0025] Pretreatment: Surface treatment of the substrate to be sprayed, and then preheating the substrate;

[0026] Preparation of nano-ceramic coating: preparing nano-ceramic coating by any of the preparation methods described above;

[0027] Spraying and curing treatment: spraying the nano ceramic coating on the surface of the preheated substrate, and then performing a curing treatment to form the nano ceramic coating on the surface of the substrate.

[0028] Furthermore, in the pre-processing step:

[0029] The surface treatment includes: performing sandblasting on the surface of the substrate so that the surface roughness of the substrate is 2.5-3 μm.

[0030] Furthermore, in the pre-processing step:

[0031] The temperature of the preheating treatment is 60~80℃; the time of the preheating treatment is 15~30min.

[0032] Furthermore, in the steps of spraying and curing:

[0033] The ambient temperature during spraying treatment is 15~30℃; the ambient humidity during spraying treatment is 50~70%; the distance between the spray gun nozzle and the substrate surface during spraying treatment is 15~25cm.

[0034] Furthermore, in the steps of spraying and curing:

[0035] The curing treatment comprises: sequentially performing low temperature curing treatment and high temperature curing treatment on the substrate;

[0036] Among them, the temperature of low-temperature curing treatment is 150~180℃, and the time of low-temperature curing treatment is 15~20min; the temperature of high-temperature curing treatment is 200~350℃, and the time of high-temperature curing treatment is 15~20min.

[0037] Furthermore, the thickness of the nano ceramic coating is 15-25 μm; the nano ceramic coating is a mesh structure; nano particles are dispersed on the mesh structure;

[0038] The nanoparticles include nano silicon dioxide, nano aluminum oxide, nano copper chromite, nano manganese dioxide and nano graphite.

[0039] Compared with the prior art, the present invention has at least the following beneficial effects:

[0040] 1. The present invention provides a nano ceramic coating, wherein the raw materials of the nano ceramic coating include silica sol solution, polysiloxane and additives; wherein the additives include fillers, and the fillers are nano powders; wherein the weight ratio of the silica sol solution, polysiloxane and additives is 1:0.5~0.8:1~2. Here, the above scheme is explained as follows: silica sol and polysiloxane are used as film-forming agents. When sprayed on the surface of the substrate and cured, the silica sol and polysiloxane are cross-linked to form bonds (i.e., a three-dimensional network structure is formed), which can reduce the excessive tensile stress caused by the bond contraction between the sol particles and the surface of the substrate, and avoid the self-cracking of the formed coating; at the same time, nano powder is used as a filler to fill the molecular gaps after the silica sol is dehydrated and condensed, and to pin the formed coating as a reinforcement, thereby improving the density of the coating and ensuring that the formed coating has no microcracks. On the one hand, it can avoid oil and dirt remaining in the coating, ensuring good easy cleaning, and on the other hand, it can avoid the coating from falling off, greatly blocking the ion penetration corrosion of the coating and the substrate.

[0041] 2. Furthermore, silica sol is a colloidal solution of nano-scale SiO2 particles uniformly dispersed in water. It has the characteristics of high surface energy, large specific surface area, high temperature resistance, corrosion resistance, and high hardness of the coating. After curing, it forms a silicon oxygen network structure (film) with polysiloxane through dehydration condensation. The silicon oxygen network structure has a strong adsorption effect and can carry nanoparticles such as aluminum oxide, copper chromite, manganese dioxide, and graphite. Since these nanoparticles themselves have high melting points, they have extremely strong temperature creep resistance at high temperatures and do not undergo phase change and oxidation. Therefore, the prepared nano-ceramic coating has good high temperature resistance.

[0042] 3. Furthermore, nano-graphite powder is added to the ceramic coating of the present invention. The nano-graphite has a large surface activity and a microscopic layered structure. It is filled in the grid (i.e., the silicon-oxygen network structure) of the ceramic coating and can form a lubricating film on the surface of the substrate to enhance the friction and wear resistance of the coating.

[0043] 4. On the other hand, the present invention provides a nano-ceramic coating, which is formed on the surface of a substrate by the above-mentioned nano-ceramic coating. On the basis of the above, the nano-ceramic coating prepared by the present invention is highly dense and non-porous, and has the comprehensive properties of being easy to clean and grease-proof, ion penetration corrosion-resistant, wear-resistant and scratch-resistant, and resistant to high-temperature oxidation failure. It can be used as a coating for protective treatment of metal surfaces of electrical appliances such as cookware, ovens, range hoods, and gas stove tops.

[0044] 5. In another aspect, the present invention provides a method for preparing a nano ceramic coating, wherein the nano ceramic coating is sprayed on the surface of a substrate by high pressure gas power spraying technology, and then cured to cause a sol-gel reaction between the raw materials of the nano ceramic coating, i.e., a condensation reaction between silica sol and polysiloxane forms a silicon oxygen network structure (three-dimensional network structure), and then a filler is filled into the silicon oxygen network structure to form a dense, non-porous nano ceramic coating; wherein the spraying effect is ensured by controlling the spraying environment, the distance of the spray gun, and the thickness of the coating, and the dual temperature zone curing process is adopted to avoid the phenomenon of cracking and loss of gloss during curing of the nano ceramic coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0046] Figure 1 The surface microstructure of the nano ceramic coating prepared in the embodiment of the present invention;

[0047] Figure 2 Flow chart of preparing nano ceramic coating of the present invention. DETAILED DESCRIPTION

[0048] In order to more clearly illustrate the implementation methods of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for the implementation methods or the description of the prior art. The drawings described below are only exemplary, and for ordinary technicians in this field, other implementation drawings can be derived from the provided drawings without creative work.

[0049] In one aspect, the present invention provides a nano ceramic coating, which comprises: a silica sol solution, polysiloxane and an additive; the additive comprises a filler, and the filler is a nano powder;

[0050] Wherein, the weight ratio of silica sol solution, polysiloxane and additive is 1:0.5~0.8:1~2.

[0051] The silica sol solution comprises, by weight, 60-70 parts of deionized water and 30-40 parts of nano-silicon dioxide particles; the dispersion of nano-silicon dioxide particles in water is prepared by using an ion exchange method, a one-step hydrolysis method of silicon powder, a silane hydrolysis method, etc., and the dispersion contains a large amount of water and hydroxyl groups; the nano-silicon dioxide particles are spherical or irregularly spherical; the average particle size D50 of the nano-silicon dioxide particles is less than 20 nm;

[0052] In parts by weight, the polysiloxane (solution) comprises (100 parts) polydimethylsiloxane;

[0053] The additives include fillers, defoamers and dispersants; in parts by weight, the additives specifically include the following components: 5-10 parts of water, 3-8 parts of nano-aluminum oxide powder, 15-30 parts of nano-copper chromite powder, 3-5 parts of nano-manganese dioxide powder, 6-10 parts of nano-graphite powder, 20-25 parts of methanol, 10-15 parts of isopropanol, 10-15 parts of propylene glycol methyl ether and 3-5 parts of defoamers;

[0054] Among them, nano-aluminum oxide powder, nano-copper chromite powder, nano-manganese dioxide powder and nano-graphite powder are fillers, and the average particle size D50 is less than 30nm; nano-aluminum oxide powder can significantly improve the hardness, wear resistance, scratch resistance, dispersibility and stability of the coating, as well as anti-pollution, fire resistance and brightening effect; nano-copper chromite powder is a high-performance inorganic pigment with the characteristics of high temperature resistance, acid and alkali resistance, solvent resistance, non-migration and easy dispersion; nano-manganese dioxide powder can significantly improve the weather resistance, aging resistance and wear resistance of the coating; nano-graphite powder has the effect of lubrication and high temperature resistance, which can further improve the easy cleaning of the coating; these fillers work together to make the prepared coating have the comprehensive properties of easy cleaning and oil resistance, ion penetration corrosion resistance, wear resistance and scratch resistance, and high temperature oxidation failure resistance;

[0055] Methanol, isopropanol and propylene glycol methyl ether are used as dispersants to improve the fluidity and dispersibility of the coating, improve the dispersion of suspended particles (fillers), prevent the sedimentation and agglomeration of nano-ions, promote the drying of the coating, plasticize the coating and reduce the film-forming temperature; the defoaming agent adopts a polyether defoaming agent.

[0056] On the other hand, the present invention provides a method for preparing the nano ceramic coating as described in any one of the above, comprising: mixing a silica sol solution and polysiloxane to obtain a mixed solution, and then mixing the mixed solution with an additive to obtain a nano ceramic coating. The specific preparation method is described in the preparation method of the nano ceramic coating described below.

[0057] In another aspect, the present invention provides an application of any of the above-mentioned nano-ceramic coatings, specifically, spraying the nano-ceramic coating onto a substrate to form a nano-ceramic coating on the substrate; wherein the substrate includes a gas stove and an oven.

[0058] The nano-ceramic coating is sprayed onto the surface of the gas cooktop or the inner wall of the oven to form a nano-ceramic coating on the surface of the gas cooktop or the inner wall of the oven.

[0059] In another aspect, the present invention provides a nano ceramic coating, which is formed by spraying any of the above nano ceramic coatings on the surface of a substrate.

[0060] Based on the above-mentioned nano-ceramic coating, silica sol and polysiloxane are used as film-forming agents. When sprayed onto the surface of the substrate and cured, the silica sol and the polysiloxane are condensed and cross-linked to form bonds, which can reduce the excessive tensile stress caused by the bond contraction between the sol particles and the surface of the substrate, and avoid the self-cracking of the formed coating; at the same time, nano-powder is used as a filler to fill the molecular gaps after the dehydration and condensation of the silica sol, and to pin the formed coating as a reinforcement, thereby improving the density of the coating and ensuring that the formed coating has no microcracks. On the one hand, it can avoid oil and dirt from remaining in the coating and ensure good easy cleaning performance; on the other hand, it can avoid the coating from falling off, greatly blocking the ion penetration corrosion of the coating and the substrate.

[0061] Among them, after the sol is cross-linked and cured on the surface of the substrate, the surface of the coating is composed of Si-O-Si bonds. The Si-bond energy is very large, the rigidity of the silica sol coating is strong, and the film formed by the coating is dense, tough, high in hardness, and good in wear resistance. However, during the gelation process, the cohesive force acting in the film will cause the bonds between the sol particles and the surface of the substrate to shrink. Excessive cohesive force will cause the coating to crack. The present invention mainly modifies the silica sol through polysiloxane. The modified silica sol is cross-linked with the polysiloxane through condensation polymerization to form bonds, which makes up for the excessive tensile stress between molecules. At the same time, a large number of nanoparticles in the filler fill the gaps, play a pinning role, and prevent the coating from cracking.

[0062] In another aspect, the present invention provides a method for preparing the above-mentioned nano ceramic coating, comprising the following steps:

[0063] Pretreatment (step S1): performing surface treatment on the substrate to be sprayed, and then preheating the substrate;

[0064] The surface of the substrate is treated by sandblasting. The first purpose is to remove grease, dust, stubborn stains, rust and other pollutants on the surface of the substrate to ensure the uniform adhesion of the ceramic coating. The second purpose is to make the metal surface have a certain degree of roughness. Before spraying, the substrate is preheated for 15-30 minutes to ensure that the surface temperature of the component is 60-80℃ during spraying.

[0065] Among them, 50 mesh and 80 mesh mixed brown corundum sand is used, with 50 mesh and 80 mesh sand accounting for half each. The surface of the treated metal (substrate) is required to reach a roughness of about 2.5~3 microns, and then it is cleaned with high-compressed air;

[0066] Preparation of nano ceramic coatings:

[0067] Step S2: preparing a silica sol solution, polysiloxane and an additive respectively, and then using a high-speed disperser to disperse the silica sol solution and the additive respectively at a speed of 400-500 r / min for at least 1 hour until there is no precipitation on the inner wall and the bottom of the container; the dispersion treatment not only allows the components of the silica sol solution to reach the sol system, but also ensures that the silica sol solution and the additive are evenly dispersed to avoid particle precipitation;

[0068] Step S3: mixing the silica sol solution and the polysiloxane to obtain a mixed solution, and then dispersing the mixed solution for at least 1.5 hours using a dual-axis dual-axis rotating machine at a speed of 100-150 r / min; after mixing, ensuring that the cylindrical container remains sealed to prevent the mixed solution from dehydrating; wherein the mixed solution and the additives after the dispersion treatment are left standing for no more than 30 minutes to avoid stratification of the liquid and sedimentation of the nanoparticles when the standing time is too long;

[0069] Finally, the mixed liquid and the additive are mixed evenly, and then a double-shaft double-shaft rotating machine is used to disperse the mixed liquid and the additive at a speed of 100-150r / min. After being dispersed evenly, a 400-mesh screen is used to filter the mixed liquid to obtain a nano ceramic coating.

[0070] Spraying and curing treatment:

[0071] Step S4: using a spray robot, using compressed air to form a negative pressure after flowing through the nozzle of the spray gun, and then sucking the paint under the action of the negative pressure, and atomizing the nano-ceramic paint after being sprayed out by the spray gun, and the atomized paint is gradually sprinkled and attached to the surface of the substrate;

[0072] Among them, the control of the spraying environment is crucial to ensure the reliability and stability of the coating. The ambient temperature for spraying is 15~30℃; the ambient humidity is controlled at 50~70%; the mechanical arm of the spraying robot can move in multiple degrees of freedom in space to ensure that the workpiece is sprayed from all angles and distances; through program presets, the robot can control the movement trajectory, speed and spray thickness of the spray gun, and the built-in sensor monitors the spraying process and coating quality in real time to ensure that each spraying achieves the preset effect; specifically, the spray gun equipped with the spray robot has a caliber of 0.5~1.5mm, a spraying pressure of 0.5~0.8MPa, and a distance of 15~25cm between the spray gun nozzle and the workpiece; according to the requirements of different components (substrates), the thickness of the coating is strictly controlled to be 15~25μm;

[0073] Step S5: After spraying, curing treatment is performed to form a nano-ceramic coating on the surface of the substrate;

[0074] The curing process is divided into two steps: first, the components with sprayed coating are placed in a curing furnace in the low-temperature zone, the temperature of the low-temperature curing treatment is set to 150~180℃, and the time of the low-temperature curing treatment is 15~20min; then the components with sprayed coating are placed in a curing furnace in the high-temperature zone, the temperature of the high-temperature curing treatment is set to 200~300℃, and the time of the high-temperature treatment is 15~20min.

[0075] In the above preparation method, after the nano-ceramic coating is sprayed onto the surface of the substrate, a curing treatment is performed, and the raw materials of the nano-ceramic coating undergo a sol-gel reaction, which can be specifically divided into four stages:

[0076] The first stage: the silane monomer (polysiloxane) in the nano-ceramic coating is hydrolyzed in the aqueous environment to generate silanol, i.e. -Si-(OR)2+H2O→-Si(OH)2+ROH. At the same time, sufficient -Si-OH groups are formed in the hydrolyzed solution; wherein R is methyl;

[0077] The second stage: silanol undergoes random polycondensation reaction to generate small molecular oligomers; -Si-OH groups can dehydrate and condense to form oligomeric silanols;

[0078] The third stage: a part of small molecular oligomers and silanols (including the above-mentioned oligomeric silanols and silanols that have not undergone polycondensation) undergo polycondensation with the silanol groups on the surface of SiO2 particles in the silica sol, and finally polymerize into a three-dimensional network structure;

[0079] The fourth stage: -Si-OH in another part of the oligomer forms hydrogen bonds with the hydroxyl -OH on the metal (substrate) surface, and -Si-OH further dehydrates and polymerizes with the hydroxyl -OH on the metal surface to form Si-O-Me covalent bonds on the workpiece (component) interface. The reaction is: -Si-OH (solution) + Me-OH (metal surface) → Si-O-Me (interface) + H2O, and dehydrates and condenses at high temperature to form a coating that is densely attached to the metal surface.

[0080] The three-dimensional network structure has a strong adsorption effect and can carry nanoparticles such as aluminum oxide, copper chromite, manganese dioxide, and graphite to form a dense network structure. Ions can penetrate without gaps and have high corrosion resistance. These nanoparticles themselves have a high melting point and have extremely strong temperature-resistant creep properties at high temperatures, with significant high-temperature resistance. Nanoparticles have a pinning effect on the coating matrix as a reinforcement, and have the hardness of metal oxide ceramics. In addition, graphite itself has a lubricating effect, which makes the coating anti-friction and wear-reducing. After the silica sol is condensed, the nano-SiO2 particles are arranged in order at the microscopic level to form a highly hydrophobic bionic structure, which appears uneven at the microscopic level and smooth at the macroscopic level, making the coating easy to clean and resistant to oil stains.

[0081] The present invention is further described below in conjunction with specific examples and comparative examples. The components of the additives in the examples are shown in Table 1 in parts by weight.

[0082] Table 1 Composition of additives in the examples

[0083]

[0084] The specific embodiments are as follows:

[0085] Example 1

[0086] The embodiment of the present invention provides a method for preparing a nano ceramic coating. The preparation process is as follows: Figure 2 As shown,

[0087] The weight ratio of silica sol solution, polysiloxane and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 70 parts of deionized water, 30 parts of nano silicon dioxide particles, 100 parts of polydimethylsiloxane of polysiloxane, and the additive includes 5 parts of water, 8 parts of nano aluminum oxide powder, 15 parts of nano copper chromite powder, 4 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 15 parts of isopropanol and 10 parts of propylene glycol methyl ether.

[0088] The specific steps include:

[0089] Pretreatment (step S1): performing surface treatment on the substrate to be sprayed, and then preheating the substrate;

[0090] The surface treatment of the substrate is carried out by sandblasting mechanical treatment. Specifically, the surface of the component is evenly treated by sandblasting with a mixture of 50 mesh and 80 mesh brown corundum sand, with 50 mesh and 80 mesh sand accounting for half each. After treatment, the surface of the substrate is required to reach a roughness of 2.8μm, and then it is cleaned with high-compressed air; the preheating time is 20 minutes, and the preheating treatment ensures that the surface temperature of the substrate is 65°C during spraying;

[0091] Preparation of nano ceramic coatings:

[0092] Step S2: preparing a silica sol solution, polysiloxane, and an additive respectively, and then using a high-speed disperser to disperse the silica sol solution and the additive respectively at a speed of 500 r / min for 1.5 hours until there is no precipitation on the inner wall and bottom of the container;

[0093] Step S3: mixing the silica sol solution and the polysiloxane to obtain a mixed solution, and then dispersing the mixed solution for 12 hours using a double-shaft double-shaft rotating machine at a speed of 150 r / min;

[0094] Finally, the mixed liquid and the additive are mixed evenly, and then a double-shaft double-shaft rotating machine is used to disperse the mixed liquid and the additive at a speed of 150r / min. After the mixture is evenly dispersed, it is filtered through a 400-mesh net to obtain a nano ceramic coating;

[0095] Spraying and curing treatment:

[0096] Step S4: using a spray robot, using compressed air to form a negative pressure after flowing through the nozzle of the spray gun, and then sucking the paint under the action of the negative pressure, and atomizing the nano-ceramic paint after being sprayed out by the spray gun, and the atomized paint is gradually sprinkled and attached to the surface of the substrate;

[0097] The spraying environment temperature is 20℃; the environmental humidity is controlled at 60%; the spray gun caliber carried by the spraying robot is 1mm, the spraying pressure is 0.6MPa, and the distance between the spray gun nozzle and the workpiece is 20cm; according to the requirements of different components (substrates), the coating thickness is strictly controlled to be 20μm;

[0098] Step S5: After spraying, curing treatment is performed to form a nano-ceramic coating on the surface of the substrate;

[0099] The curing process is divided into two steps: the temperature of the low-temperature curing process is set to 150°C, and the time of the low-temperature curing process is 15 minutes; the temperature of the high-temperature curing process is set to 300°C, and the time of the high-temperature curing process is 15 minutes.

[0100] Example 2

[0101] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 70 parts of deionized water, 30 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 8 parts of nano aluminum oxide powder, 20 parts of nano copper chromite powder, 4 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 15 parts of isopropanol and 10 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 1.

[0102] Example 3

[0103] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 70 parts of deionized water, 30 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 8 parts of nano aluminum oxide powder, 30 parts of nano copper chromite powder, 4 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 30 parts of methanol, 15 parts of isopropanol and 10 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 1.

[0104] Example 4

[0105] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 70 parts of deionized water, 30 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 3 parts of nano aluminum oxide powder, 20 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 25 parts of methanol, 15 parts of isopropanol and 15 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 1.

[0106] Example 5

[0107] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 70 parts of deionized water, 30 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 3 parts of nano aluminum oxide powder, 20 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 8 parts of nano graphite powder, 25 parts of methanol, 10 parts of isopropanol and 15 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 1.

[0108] Example 6

[0109] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 70 parts of deionized water, 30 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 3 parts of nano aluminum oxide powder, 20 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 10 parts of nano graphite powder, 25 parts of methanol, 10 parts of isopropanol and 15 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 1.

[0110] Example 7

[0111] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane, and additive is 1:0.5:1; in terms of weight, the silica sol solution includes 60 parts of deionized water, 40 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 5 parts of nano aluminum oxide powder, 25 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 12 parts of isopropanol, and 12 parts of propylene glycol methyl ether;

[0112] The specific steps include:

[0113] Pretreatment (step S1): performing surface treatment on the substrate to be sprayed, and then preheating the substrate;

[0114] The surface treatment of the substrate is carried out by sandblasting mechanical treatment. Specifically, the surface of the component is evenly treated with 50-mesh and 80-mesh mixed brown corundum sand, with 50-mesh and 80-mesh sand accounting for half each. After treatment, the surface of the substrate is required to reach a roughness of 2.5μm, and then it is cleaned with high-compressed air; the preheating time is 15 minutes, and the preheating treatment ensures that the surface temperature of the substrate is 60°C during spraying;

[0115] Preparation of nano ceramic coatings:

[0116] Step S2: preparing a silica sol solution, polysiloxane, and an additive respectively, and then using a high-speed disperser to disperse the silica sol solution and the additive respectively at a speed of 400 r / min for 1.5 hours until there is no precipitation on the inner wall and bottom of the container;

[0117] Step S3: mixing the silica sol solution and the polysiloxane to obtain a mixed solution, and then dispersing the mixed solution for 1.5 hours using a double-shaft double-shaft rotating machine at a speed of 100 r / min;

[0118] Finally, the mixed liquid and the additive are mixed evenly, and then a double-shaft double-shaft rotating machine is used to disperse the mixed liquid and the additive at a speed of 100r / min. After being dispersed evenly, a 400-mesh screen is used to filter the mixed liquid to obtain a nano ceramic coating.

[0119] Spraying and curing treatment:

[0120] Step S4: using a spray robot, using compressed air to form a negative pressure after flowing through the nozzle of the spray gun, and then sucking the paint under the action of the negative pressure, and atomizing the nano-ceramic paint after being sprayed out by the spray gun, and the atomized paint is gradually sprinkled and attached to the surface of the substrate;

[0121] The spraying environment temperature is 15℃; the environmental humidity is controlled at 50%; the spray gun caliber carried by the spray robot is 0.5mm, the spraying pressure is 0.5MPa, and the distance between the spray gun nozzle and the workpiece is 15cm; according to the requirements of different components (substrates), the coating thickness is strictly controlled to be 15μm;

[0122] Step S5: After spraying, curing treatment is performed to form a nano-ceramic coating on the surface of the substrate;

[0123] The curing process is divided into two steps: the temperature of the low-temperature curing process is set to 150°C, and the time of the low-temperature curing process is 15 minutes; the temperature of the high-temperature curing process is set to 300°C, and the time of the high-temperature curing process is 15 minutes.

[0124] Example 8

[0125] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:1.3; in terms of weight, the silica sol solution includes 60 parts of deionized water, 40 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 5 parts of nano aluminum oxide powder, 25 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 12 parts of isopropanol and 12 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 7.

[0126] Example 9

[0127] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:1.6; in terms of weight, the silica sol solution includes 60 parts of deionized water, 40 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 5 parts of nano aluminum oxide powder, 25 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 12 parts of isopropanol and 12 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 7.

[0128] Example 10

[0129] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:2; in terms of weight, the silica sol solution includes 60 parts of deionized water, 40 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 5 parts of nano aluminum oxide powder, 25 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 12 parts of isopropanol and 12 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 7.

[0130] Embodiment 11

[0131] The present embodiment provides a method for preparing a nano ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane, and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 60 parts of deionized water, 40 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 5 parts of nano aluminum oxide powder, 25 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 12 parts of isopropanol, and 12 parts of propylene glycol methyl ether;

[0132] The specific steps include:

[0133] Pretreatment (step S1): performing surface treatment on the substrate to be sprayed, and then preheating the substrate;

[0134] The surface treatment of the substrate is carried out by sandblasting mechanical treatment. Specifically, the surface of the component is evenly treated with 50-mesh and 80-mesh mixed brown corundum sand, with 50-mesh and 80-mesh sand accounting for half each. After treatment, the surface of the substrate is required to reach a roughness of 3μm, and then it is cleaned with high-compressed air; the preheating time is 30 minutes, and the preheating treatment ensures that the surface temperature of the substrate is 80°C during spraying;

[0135] Preparation of nano ceramic coatings:

[0136] Step S2: preparing a silica sol solution, polysiloxane, and an additive respectively, and then using a high-speed disperser to disperse the silica sol solution and the additive respectively at a speed of 500 r / min for 2 hours until there is no precipitation on the inner wall and bottom of the container;

[0137] Step S3: mixing the silica sol solution and the polysiloxane to obtain a mixed solution, and then dispersing the mixed solution for 3 hours using a double-shaft double-shaft rotating machine at a speed of 150 r / min;

[0138] Finally, the mixed liquid and the additive are mixed evenly, and then a double-shaft double-shaft rotating machine is used to disperse the mixed liquid and the additive at a speed of 150r / min. After the mixture is evenly dispersed, it is filtered through a 400-mesh net to obtain a nano ceramic coating;

[0139] Spraying and curing treatment:

[0140] Step S4: using a spray robot, using compressed air to form a negative pressure after flowing through the nozzle of the spray gun, and then sucking the paint under the action of the negative pressure, and atomizing the nano-ceramic paint after being sprayed out by the spray gun, and the atomized paint is gradually sprinkled and attached to the surface of the substrate;

[0141] The spraying environment temperature is 30℃; the environmental humidity is controlled at 70%; the spray gun caliber carried by the spray robot is 1.5mm, the spraying pressure is 0.8MPa, and the distance between the spray gun nozzle and the workpiece is 15~25cm; according to the requirements of different components (substrates), the coating thickness is strictly controlled to be 25μm;

[0142] Step S5: After spraying, curing treatment is performed to form a nano-ceramic coating on the surface of the substrate;

[0143] The curing process is divided into two steps: the temperature of the low-temperature curing process is set to 150°C, and the time of the low-temperature curing process is 15 minutes; the temperature of the high-temperature curing process is set to 200°C, and the time of the high-temperature curing process is 15 minutes.

[0144] Example 12

[0145] The present embodiment provides a method for preparing a nano ceramic coating, which is prepared specifically according to the above steps; wherein the weight ratio of the silica sol solution, polysiloxane, and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 60 parts of deionized water, 40 parts of nano silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 5 parts of nano aluminum oxide powder, 25 parts of nano copper chromite powder, 5 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 12 parts of isopropanol, and 12 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 11.

[0146] Embodiment 13

[0147] The present embodiment provides a method for preparing a nano-ceramic coating, wherein the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 60 parts of deionized water, 40 parts of nano-silicon dioxide particles, the polysiloxane is 100 parts of polydimethylsiloxane, and the additive includes 5 parts of water, 5 parts of nano-aluminum oxide powder, 25 parts of nano-copper chromite powder, 5 parts of nano-manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano-graphite powder, 20 parts of methanol, 12 parts of isopropanol and 12 parts of propylene glycol methyl ether; the specific preparation steps are the same as those in Example 11.

[0148] Comparative Example 1

[0149] This comparative example provides a method for preparing a nano ceramic coating, comprising the following steps:

[0150] Pretreatment (step S1): performing surface treatment on the substrate to be sprayed, and then preheating the substrate;

[0151] The surface treatment of the substrate is carried out by sandblasting mechanical treatment. Specifically, the surface of the component is evenly treated with 50-mesh and 80-mesh mixed brown corundum sand, with 50-mesh and 80-mesh sand accounting for half each. After treatment, the surface of the substrate is required to reach a roughness of 2.8μm, and then it is cleaned with high-compressed air; the preheating time is 20min, and the preheating treatment ensures that the surface temperature of the substrate is 65℃ during spraying;

[0152] Preparation of nano ceramic coatings:

[0153] Step S2: preparing a silica sol solution and an additive respectively, and then using a high-speed disperser to disperse the silica sol solution and the additive respectively at a speed of 500 r / min for 1.5 hours until there is no precipitation on the inner wall and the bottom of the container;

[0154] The weight ratio of the silica sol solution to the additive is 1:1.5; in terms of weight, the silica sol solution includes 70 parts of deionized water, 30 parts of nano silicon dioxide particles, and the additives include 5 parts of water, 8 parts of nano aluminum oxide powder, 15 parts of nano copper chromite powder, 4 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 15 parts of isopropanol, and 10 parts of propylene glycol methyl ether.

[0155] Step S3: uniformly mixing the silica sol solution and the additive, and then dispersing the mixed solution and the additive using a double-shaft double-shaft rotating machine at a speed of 150 r / min, and filtering the mixed solution using a 400-mesh screen to obtain a nano ceramic coating after uniform dispersion;

[0156] Spraying and curing treatment:

[0157] Step S4: using a spray robot, using compressed air to form a negative pressure after flowing through the nozzle of the spray gun, and then sucking the paint under the action of the negative pressure, and atomizing the nano-ceramic paint after being sprayed out by the spray gun, and the atomized paint is gradually sprinkled and attached to the surface of the substrate;

[0158] The spraying environment temperature is 20℃; the environmental humidity is controlled at 60%; the spray gun caliber carried by the spray robot is 1mm, the spraying pressure is 0.6MPa, and the distance between the spray gun nozzle and the workpiece is 20cm; according to the requirements of different components (substrates), the coating thickness is strictly controlled to be 20μm;

[0159] Step S5: After spraying, curing treatment is performed to form a nano-ceramic coating on the surface of the substrate;

[0160] The curing treatment is divided into two steps: first, the components with sprayed coating are placed in a curing treatment furnace in the low-temperature zone, the temperature of the low-temperature curing treatment is set to 150°C, and the time of the low-temperature curing treatment is 15 minutes; then the components with sprayed coating are placed in a curing treatment furnace in the high-temperature zone, the temperature of the high-temperature curing treatment is set to 300°C, and the time of the high-temperature treatment is 15 minutes.

[0161] Comparative Example 2

[0162] This comparative example provides a method for preparing a nano ceramic coating, comprising the following steps:

[0163] Pretreatment (step S1): performing surface treatment on the substrate to be sprayed, and then preheating the substrate;

[0164] The surface treatment of the substrate is carried out by sandblasting mechanical treatment. Specifically, the surface of the component is evenly treated with 50-mesh and 80-mesh mixed brown corundum sand, with 50-mesh and 80-mesh sand accounting for half each. After treatment, the surface of the substrate is required to reach a roughness of 2.8μm, and then it is cleaned with high-compressed air; the preheating time is 20min, and the preheating treatment ensures that the surface temperature of the substrate is 65℃ during spraying;

[0165] Preparation of nano ceramic coatings:

[0166] Step S2: preparing a silica sol solution, polysiloxane, and an additive respectively, and then using a high-speed disperser to disperse the silica sol solution and the additive respectively at a speed of 400-500 r / min for at least 1 hour until there is no precipitation on the inner wall and bottom of the container;

[0167] The weight ratio of silica sol solution, polysiloxane and additive is 1:0.5:1.5; in terms of weight, the silica sol solution includes 70 parts of deionized water, 30 parts of nano silicon dioxide particles, 100 parts of polydimethylsiloxane of polysiloxane, and the additive includes 5 parts of water, 8 parts of nano aluminum oxide powder, 15 parts of nano copper chromite powder, 4 parts of nano manganese dioxide powder, 3 parts of defoaming agent, 6 parts of nano graphite powder, 20 parts of methanol, 15 parts of isopropanol and 10 parts of propylene glycol methyl ether.

[0168] Step S3: mixing the silica sol solution and the polysiloxane to obtain a mixed solution, and then dispersing the mixed solution for 12 hours using a double-shaft double-shaft rotating machine at a speed of 150 r / min;

[0169] Finally, the mixed liquid and the additive are mixed evenly, and then a double-shaft double-shaft rotating machine is used to disperse the mixed liquid and the additive at a speed of 100-150r / min. After being dispersed evenly, a 400-mesh screen is used to filter the mixed liquid to obtain a nano ceramic coating.

[0170] Spraying and curing treatment:

[0171] Step S4: using a spray robot, using compressed air to form a negative pressure after flowing through the nozzle of the spray gun, and then sucking the paint under the action of the negative pressure, and atomizing the nano-ceramic paint after being sprayed out by the spray gun, and the atomized paint is gradually sprinkled and attached to the surface of the substrate;

[0172] The spraying environment temperature is 20℃; the environmental humidity is controlled at 60%; the spray gun caliber carried by the spraying robot is 1mm, the spraying pressure is 0.6MPa, and the distance between the spray gun nozzle and the workpiece is 20cm; according to the requirements of different components (substrates), the coating thickness is strictly controlled to be 20μm;

[0173] Step S5: After spraying, curing treatment is performed to form a nano-ceramic coating on the surface of the substrate;

[0174] The curing treatment is divided into two steps: first, the components with sprayed coating are placed in a curing treatment furnace in the low-temperature zone, the temperature of the low-temperature curing treatment is set to 150°C, and the time of the low-temperature curing treatment is 15 minutes; then the components with sprayed coating are placed in a curing treatment furnace in the high-temperature zone, the temperature of the high-temperature curing treatment is set to 150°C, and the time of the high-temperature treatment is 15 minutes.

[0175] The nano-ceramic coatings prepared in the embodiments of the present invention and the comparative examples were tested for corrosion resistance (immersed in a 6% FeCl3 solution for 240 hours to check the coating shedding), wear resistance (applying a 1000g weight, 100r / min, and a rubber wheel friction and wear test for 10min), contact angle, hardness (tested according to the GB / T 6739-2006 paint and varnish pencil method for measuring the hardness of the paint film), high temperature resistance (500°C, 5h insulation treatment), bonding strength test (tested according to the GB / T 9286-1998 "Scratch test for paint and varnish films" standard test), and easy cleanability (tested by wiping with a scouring pad after baking ketchup at 220°C for 15min). The specific test results are shown in Table 2.

[0176] Table 2 Performance test results of nano ceramic coatings of the present invention and comparative examples

[0177]

[0178] As can be seen from Table 2, compared with Examples 1 to 13, no polysiloxane was added in Comparative Example 1, and the comprehensive performance of the prepared nano-ceramic coating was greatly reduced, mainly because the coating had local microcracks in the microscopic performance, resulting in the coating being not dense, resulting in a decrease in corrosion resistance, wear resistance, temperature resistance, and easy-to-clean effect. This is because after the silica sol is cross-linked and cured on the surface of the substrate, the surface of the coating is composed of Si-O-Si bonds, and the Si-bond energy is very large. The silica sol coating has strong rigidity, but in the gelation process, the cohesive force acting in the coating will cause the bonds between the sol particles and the substrate surface to shrink. Excessive cohesive force will cause the coating to crack, so the lack of siloxane cross-linking causes microcracks in the coating; in Comparative Example 2, the temperature in the high-temperature zone is reduced during curing, and the dehydration and polycondensation reaction inside the coating is incomplete, which affects the hardness and corrosion resistance index of the coating. The incompletely cured coating reduces its density, and there are uniformly distributed voids at the microscopic level, and the hardness is reduced. At the same time, when doing the corrosion resistance experiment, chloride ions penetrate with the voids, causing the coating to fall off and be damaged. Therefore, the reduction of curing temperature will greatly affect the reliability and durability of the coating.

[0179] The surface microstructure of the nano ceramic coating prepared in Example 1 of the present invention is as follows: Figure 1 As shown, it can be seen that at the microscopic level, nano-SiO2 and other particles are dispersed, and the overall network structure constitutes a dense arrangement of -Si-O-Si-bonds, forming a highly hydrophobic bionic structure. At the microscopic level, it appears uneven, and at the macroscopic level, the coating appears smooth and bright, making the coating easy to clean and resistant to oil stains.

[0180] Comparative Examples 1, 2, and 3, the changes in each component have little effect on the contact angle, but the increase in the content of nano-copper chromite powder is beneficial to wear resistance, and the contact angle changes less after the friction test, which may be beneficial to the easy-to-clean effect of the coating after long-term use; Comparative Examples 4, 5, and 6, the increase in the content of the nano-graphite powder component, the macroscopic bright effect of the coating is better, the coating appears to be more hydrophobic, and after the friction test of the coating, it still has a larger contact angle, and the appropriate increase in the nano-graphite powder is beneficial to improving the lubrication and anti-wear effect of the coating; Comparative Examples 7, 8, 9, and 10, the addition of excessive or less component C filler will have a greater effect on the wear resistance of the coating, but within the range of the addition amount of the present invention, it still has excellent wear resistance; Comparative Examples 11, 12, and 13, the curing temperature in the high temperature zone affects the curing effect of the coating, and a higher temperature will make the coating cure more completely.

[0181] From the analysis of the embodiments based on the test data in the table, within the coating composition range designed by the present invention, the water-based nano-ceramic coating has excellent corrosion resistance, high temperature resistance, wear resistance, and easy cleaning properties. It can be used as an anti-corrosion and wear-resistant coating, a high-temperature easy-to-clean coating, etc. It has good weather resistance and durability, and can be used reliably for a long time in different scenarios.

[0182] It is easy for those skilled in the art to understand that, without conflict, the advantageous technical features of the above-mentioned methods can be freely combined and superimposed.

[0183] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention shall be included in the protection scope of the present invention. The above description is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and variations can be made without departing from the technical principles of the present invention. These improvements and variations should also be regarded as the protection scope of the present invention.

Claims

1. A nano ceramic coating, characterized in that: The nano ceramic coating comprises: silica sol solution, polysiloxane and additives; Wherein, the polysiloxane includes polydimethylsiloxane; the additive includes a filler, and the filler is a nano powder; the filler includes nano aluminum oxide powder, nano copper chromite powder, nano manganese dioxide powder and nano graphite powder; the additive also includes a dispersant and a defoamer; wherein the dispersant includes methanol, isopropanol, and propylene glycol methyl ether; The additive comprises the following components: 5-10 parts of water, 3-8 parts of nano aluminum oxide powder, 15-30 parts of nano copper chromite powder, 3-5 parts of nano manganese dioxide powder, 6-10 parts of nano graphite powder, 20-25 parts of methanol, 10-15 parts of isopropanol, 10-15 parts of propylene glycol methyl ether and 3-5 parts of defoaming agent; Wherein, the weight ratio of the silica sol solution, polysiloxane and additive is 1:0.5~0.8:1~2.

2. The nano ceramic coating according to claim 1, characterized in that: In parts by weight, the silica sol solution includes the following components: 60-70 parts of deionized water and 30-40 parts of nano-silicon dioxide particles.

3. The nano ceramic coating according to claim 2, characterized in that: The average particle size D50 of the nano silicon dioxide particles is less than 20 nm; the average particle size D50 of the nano aluminum oxide powder, nano copper chromite powder, nano manganese dioxide powder and nano graphite powder is less than 30 nm.

4. A method for preparing a nano ceramic coating according to any one of claims 1 to 3, characterized in that: include: The silica sol solution and polysiloxane are mixed to obtain a mixed solution, and then the mixed solution is mixed with an additive to obtain a nano ceramic coating.

5. The method for preparing the nano ceramic coating according to claim 4, characterized in that: Before the silica sol solution and the polysiloxane are mixed, the process also includes: The silica sol solution is dispersed for at least 1 hour using a high-speed disperser at a speed of 400-500 r / min.

6. An application of the nano ceramic coating according to any one of claims 1 to 3, characterized in that: The nano ceramic coating is used for spraying onto a substrate to form a nano ceramic coating on the substrate.

7. The use of the nano ceramic coating according to claim 6, characterized in that: The substrate includes a gas cooker and an oven.

8. A nano ceramic coating, characterized in that: The nano ceramic coating is formed by spraying the nano ceramic coating according to any one of claims 1 to 3 on the surface of the substrate.

9. A method for preparing a nano ceramic coating according to claim 8, characterized in that: The following steps are involved: Pretreatment: Surface treatment of the substrate to be sprayed, and then preheating of the substrate; Preparation of nano-ceramic coating: preparing the nano-ceramic coating by the preparation method described in claim 4 or 5; Spraying and curing treatment: spraying the nano ceramic coating on the surface of the preheated substrate, and then performing a curing treatment to form the nano ceramic coating on the surface of the substrate.

10. The method for preparing the nano ceramic coating according to claim 9, characterized in that: In the pre-processing steps: The surface treatment includes: performing sandblasting on the surface of the substrate so that the surface roughness of the substrate is 2.5-3 μm.

11. The method for preparing a nano ceramic coating according to claim 9 or 10, characterized in that: In the pre-processing steps: The temperature of the preheating treatment is 60~80℃; the time of the preheating treatment is 15~30min.

12. The method for preparing the nano ceramic coating according to claim 11, characterized in that: In the steps of spraying and curing: The ambient temperature during spraying treatment is 15~30℃; the ambient humidity during spraying treatment is 50~70%; the distance between the spray gun nozzle and the substrate surface during spraying treatment is 15~25cm.

13. The method for preparing the nano ceramic coating according to claim 11, characterized in that: In the steps of spraying and curing: The curing treatment comprises: sequentially performing low temperature curing treatment and high temperature curing treatment on the substrate; Among them, the temperature of low-temperature curing treatment is 150~180℃, and the time of low-temperature curing treatment is 15~20min; the temperature of high-temperature curing treatment is 200~350℃, and the time of high-temperature curing treatment is 15~20min.

14. The method for preparing a nano ceramic coating according to claim 9, characterized in that: The thickness of the nano ceramic coating is 15-25 μm; the nano ceramic coating is a mesh structure; nano particles are dispersed on the mesh structure; The nanoparticles include nano silicon dioxide, nano aluminum oxide, nano copper chromite, nano manganese dioxide and nano graphite.

Citation Information

Cited By

  • Water-based poly-ceramic protective coating material and preparation method thereof

    CN122011875A